Principles of corporate finance - Brealey, Richard D.; Myers, Stewart C. (New York : McGraw-Hill, 1996)
Business
Keywords: Corporate finance; Value; Investment; Risk management; Capital budgeting; Dividend policy; Capital structure; Investment; Price theory; Debt financing; Financial planning; Financial management